Amarogentin Displays Immunomodulatory Effects in Human Mast Cells and Keratinocytes - Ute Wölfle; Birgit Haarhaus; Christoph M. Schempp (Mediators of Inflammation)
Keratinocytes express the bitter taste receptors TAS2R1 and TAS2R38. Amarogentin as an agonist for TAS2R1 and other TAS2Rs promotes keratinocyte differentiation. Similarly, mast cells are known to express bitter taste receptors. The aim of this study was to assess whether bitter compounds display immunomodulatory effects on these immunocompetent cells in the skin, so that they might be a target in chronic inflammatory diseases such as atopic dermatitis and psoriasis. Here, we investigated the impact of amarogentin on substance P-induced release of histamine and TNF-α from the human mast cell line LAD-2. Furthermore, the effect of amarogentin on HaCaT keratinocytes costimulated with TNF-α and histamine was investigated. Amarogentin inhibited in LAD-2 cells substance P-induced production of newly synthesized TNF-α, but the degranulation and release of stored histamine were not affected. In HaCaT keratinocytes histamine and TNF-α induced IL-8 and MMP-1 expression was reduced by amarogentin to a similar extent as with azelastine. In conclusion amarogentin displays immunomodulatory effects in the skin by interacting with mast cells and keratinocytes.